Pathological and biochemical changes in intoxication of mindi (Melia azedarach) leaf - Yulvian Sani; Sjamsul Bahri (Jurnal Ilmu Ternak dan Veteriner, 1995)
The purpose of this study was to investigate pathological and biochemical changes in intoxication of mindi leaf (Melia azedarach) on skeletal muscle and myocardial tissues . Fifty two male Wistar rats weighing 140 g to 240 g were intoxicated in 20%; 25% and 40% diet of mindi leaf ad libitwn for 25 days . Clinical signs did not appear the intoxication of mindi leaf. Specific pathological changes were not found macroscopically except cachexia and paleness . Skeletal muscle lesions on the other hand, were consistently noted microscopically . There were degeneration, necrosis and fragmentation of muscle fibres ; enlargement of nuclei ; fibrosis; oedema and hyalination . The hyalination was prominent and appeared to be more. progressive two weeks after dosing . Following the skeletal muscle lesions, myocardial showed degeneration, necrosis and fragmentation of fibres ; enlargement of nuclei and hypercellularity . Regeneration of skeletal muscle developed on day-5 after the substitution of mindi diet by normal diet indicated by disappearing of hyalin tissues . But, myocardial appeared to be regenerated two days after the substitution of diet . Enzymatic activities of alanine aminotransferase (ALAI) and aspartate aminotransferase (ASAT) were not affected. Both enzymes in treated animals were lower than the control . The substitution of diet showed an increased of enzymatic activities during the first two weeks of feeding then reduced at the subsequent weeks . However, these enzymes increased on day-3 after substitution and appeared to maximum followed by a reduction of enzymatic activities in week-4 . On the other hand, creatinine phosphokinase (CPK) was affected in which higher level was noted in treated groups than control . Substitution of diet has led to the reduction of cpc level on day-2 and appeared to reach the same level as in control group on day-21 . The control group was not affected either clinically, pathologically or biochemically . It remained normal throughout the experimental period .